Immunity to infection in IL-17-deficient mice and humans - Cypowyj, Sophie (2012)
Mice with defective IL-17 immunity display a broad vulnerability to various infectious agents at diverse mucocutaneous surfaces. In humans, the study of patients with various primary immunodeficiencies, including autosomal dominant hyper-IgE syndrome caused by dominant-negative STAT3 mutations and autosomal recessive autoimmune polyendocrinopathy syndrome type 1 caused by null mutations in AIRE, has suggested that IL-17A, IL-17F and/or IL-22 are essential for mucocutaneous immunity to Candida albicans. This hypothesis was confirmed by the identification of rare patients with chronic mucocutaneous candidiasis (CMC) due to autosomal recessive IL-17RA deficiency and autosomal dominant IL-17F deficiency. Heterozygosity for gain-of-function mutations in STAT1 in additional patients with CMC was recently shown to inhibit the development of IL-17 T cells. Although the infectious phenotype of patients with CMC and inborn errors of IL-17 immunity remains to be finely delineated, it appears that human IL-17A and IL-17F display redundancy for protective immunity in natural conditions that is not seen in their mouse orthologs in experimental conditions.